Paleontology and ichnology of the late Ediacaran Nasep–Huns transition (Nama Group, southern Namibia). (July 2022) - Turk, Katherine A.; Maloney, Katie M.; Laflamme, Marc; Darroch, Simon A.F.
Abstract: The Nasep and Huns members of the Urusis Formation (Nama Group), southern Namibia, preserve some of the most diverse trace-fossil assemblages known from the latest Ediacaran worldwide, including potentially the world's oldest "complex" vertical sediment-penetrating burrows. These sediments record relatively diverse communities of bilaterian metazoans existing before the base of the Cambrian and an increase in the intensity of metazoan ecosystem engineering behaviors that could eventually produce profound changes in the character of the Phanerozoic sedimentary record (the "agronomic revolution"). Despite this, relatively little about this trace-fossil assemblage is known. We explore the Nasep–Huns transition at two localities in the Witputs sub-basin and describe the trace- and body-fossil diversity present in these horizons alongside a paleoenvironmental reconstruction. We document eight unique ichnotaxa from these localities, including well-preserved "probes" potentially left by priapulids. We also report the first occurrence of Corumbella from Namibia, helping to establish a biostratigraphic link between Namibia, Brazil, Paraguay, Iran, and the southwestern United States. Last, we find that several ichnotaxa, in particular small treptichnids, appear to be preferentially preserved on the bases of gutter casts, hinting at the potential existence of an unusual late Ediacaran preservational window with possible implications for timing the first appearance of key bilaterian behaviors.